The origin and development of the United States Army - Wilson, Bruce Steinhoff (My University, 1908)
Introduction: The United States Army was not born, in a time of peace, for conquest. It was born during the birth throes of our nation, for defense. A willful, patriotic, and vigorous race of democrats had taken possession of the New World.
Citation: Wilson, Bruce Steinhoff. The origin and development of the United States Army. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: United States; Army; Military; War; Handwritten; Graduating theses; Senior theses; Theses